2019
DOI: 10.1097/sle.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Spontaneous Pneumothorax: Pleural Abrasion or Pleurectomy?

Abstract: Purpose: A primary spontaneous pneumothorax is a condition that occurs predominantly in young and thin male individuals who do not have any history of underlying lung disease. Various techniques such as pleural abrasion and pleurectomy are used to reduce the recurrence rate, but there exists no consensus among surgeons on which surgical technique offers the lowest risk of recurrence. We aimed to compare the efficiency and recurrence risk of pleural abrasion and pleurectomy methods in patients with primary spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…We did not evaluate postoperative length of stay specifically in our study. Ocakcıoğlu and Kupeli[ 17 ] observed in their study that length of hospital stay was shorter with pleural abrasion than with pleurectomy due to less bleeding and pain and shorter time to drain removal. The authors also reported that pleural abrasion had the same effectiveness and was safer in terms of complications when compared to pleurectomy, although another study suggested that pleurectomy was more effective than abrasion and resulted in lower recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate postoperative length of stay specifically in our study. Ocakcıoğlu and Kupeli[ 17 ] observed in their study that length of hospital stay was shorter with pleural abrasion than with pleurectomy due to less bleeding and pain and shorter time to drain removal. The authors also reported that pleural abrasion had the same effectiveness and was safer in terms of complications when compared to pleurectomy, although another study suggested that pleurectomy was more effective than abrasion and resulted in lower recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight studies underwent full text review and application of inclusion criteria, following which eight studies were deemed eligible for inclusion in this review. Two studies were prospective [13,14], and remaining six studies [15][16][17][18][19][20] were retrospective in nature. All eight studies were included in the meta-analysis [12][13][14][15][16][17][18][19].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies were prospective [13,14], and remaining six studies [15][16][17][18][19][20] were retrospective in nature. All eight studies were included in the meta-analysis [12][13][14][15][16][17][18][19].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations